PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR (POC) UNTUK MASYARAKAT DESA CILEMBU KABUPATEN SUMEDANG - Wiyatna , Muhamad Fatah; Andriani , Yuli; Pratama, Rusky Intan (Universitas Mataram, 2024)
Agriculture in Sumedang Regency is the main livelihood, but the continuous use of synthetic fertilizers has caused environmental damage. The solution comes through liquid organic fertilizers from local ingredients, such as banana stump and bamboo shoots, which have a positive impact in triggering plant growth. The organic fertilizer-making training program in Cilembu Village, Sumedang Regency, is part of the CSR initiative to improve agricultural yields and farmers' independence. The target audience of this liquid organic fertilizer making training activity is the Pangkalan Farmer Group located in Cilembu Village, Pamulihan District, Sumedang Regency, which was held on Tuesday, October 31, 2023. The method of this activity is counseling and practice with expert speakers from the Faculty of Animal Husbandry UNPAD. Liquid organic fertilizer has a vital role in improving soil quality and providing plant nutrients. Despite its advantages, liquid organic fertilizer also has disadvantages, such as the low viability of microorganisms in it and limited nutrient content. The socialization of organic fertilizer production in Cilembu Village is expected to help the community utilize local resources and overcome the challenge of expensive fertilizer prices.